Turkey 2017 Clinical Practice Guidelines on recommendations for screning diagnosing and managing hepatitis C virus - Idilman, Ramazan; Baykam, Nurcan; Kaymakoğlu, Sabahattin; Tabak, Fehmi; Bahçecioğlu, Halil İ.; Bektaş, Ahmet; Bulut, Cemal; Günşar, Fulya; İnan, Dilara; Karaosmanoğlu, Hayat K.; Karasu, Zeki; Kuşçu, Ferit; et al. (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Idilman R, Baykam N; Viral Hepatitis Guidelines Study Group. Turkey 2017 Clinical Practice Guidelines on recommendations for screning diagnosing and managing hepatitis C virus. Turk J Gastroenterol 2017; 28(Suppl 2); S90-S93.